An exploratory study of EAP teachers' coping strategies. (June 2022) - Nazari, Ogholgol; Atai, Mahmood Reza
Abstract: English for Academic Purposes (EAP) teachers are expected to cope with the manifold challenges of teaching EAP courses although they do not generally receive adequate training for handling them. Therefore, this study explored the coping strategies used by them upon facing different challenges and probed the effectiveness of these strategies. To this end, we collected quantitative data from 314 EAP teachers through a questionnaire developed for the purposes of this study and conducted semi-structured interviews with 30 teachers chosen from those who completed the questionnaire and volunteered to participate in the interview. The results revealed the coping strategies used by the participants of the study and highlighted the effective ones. The findings provide implications for current and prospective EAP teachers as well as teacher educators by presenting some effective strategies for EAP instruction.